2021
DOI: 10.1371/journal.pone.0250768
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of hyaluronic acid injection versus extracorporeal shockwave therapy on chronic plantar fasciitis: Protocol for a randomized controlled trial

Abstract: Background Plantar fasciitis is the most common cause of pain in the plantar region of the heel, and extracorporeal shockwave therapy (ESWT) is an option used in cases where conservative treatment fails. Hyaluronic acid (HA), initially used for osteoarthrosis, is a treatment option because it has been applied to extra-articular regions, such as tendons, ligaments, and fascia. The aim of the present study will be to evaluate the outcomes of pain, function, and personal satisfaction after a single injection of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Several preclinical and clinical studies have reported on the therapeutic applications of hyaluronan in managing fasciopathies, tendinopathies, and osteoarthritis, all of which share important pathophysiological mechanisms [ 18 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 ]. In an animal model of osteoarthritis, administration of hyaluronan to isolated medial articular nerves dramatically lowered both ongoing and movement-evoked nerve activities, indicating a therapeutically important antinociceptive activity in inflamed joints through an elastoviscous, rheological effect on nociceptive afferent fibers [ 147 ].…”
Section: Therapeutic Considerations Of Hyaluronan In Myofascial Diseasementioning
confidence: 99%
“…Several preclinical and clinical studies have reported on the therapeutic applications of hyaluronan in managing fasciopathies, tendinopathies, and osteoarthritis, all of which share important pathophysiological mechanisms [ 18 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 ]. In an animal model of osteoarthritis, administration of hyaluronan to isolated medial articular nerves dramatically lowered both ongoing and movement-evoked nerve activities, indicating a therapeutically important antinociceptive activity in inflamed joints through an elastoviscous, rheological effect on nociceptive afferent fibers [ 147 ].…”
Section: Therapeutic Considerations Of Hyaluronan In Myofascial Diseasementioning
confidence: 99%